The Role of Neutrophils in Transplanted Organs. Issue 2 (25th July 2016) - Scozzi, D.; Ibrahim, M.; Menna, C.; Krupnick, A. S.; Kreisel, D.; Gelman, A. E.
Abstract : Neutrophils are often viewed as nonspecialized effector cells whose presence is a simple indicator of tissue inflammation. There is new evidence that neutrophils exist in subsets and have specialized effector functions that include extracellular trap generation and the stimulation of angiogenesis. The application of intravital imaging to transplanted organs has revealed novel requirements for neutrophil trafficking into graft tissue and has illuminated direct interactions between neutrophils and other leukocytes that promote alloimmunity. Paradoxically, retaining some neutrophilia may be important to induce or maintain tolerance. Neutrophils can stimulate anti‐inflammatory signals in other phagocytes and release molecules that inhibit T cell activation. In this article, we will review the available evidence of how neutrophils regulate acute and chronic inflammation in transplanted organs and discuss the possibility of targeting these cells to promote tolerance. Abstract : New insights into neutrophil function reveal their important role in stimulating alloimmunity as well as their potential for tolerance promotion.